Diagnostic value of fluid‐based non‐amyloid biomarkers for Alzheimer's disease and related dementias in a clinic‐based cohort from South Asia - Faheem Arshad; M. M. Samim; Paras Rohidas Borse; Ravi G. Shankar; R. Bharath; B. H. Gagantej; Pooja Mailankody; Subasree Ramakrishnan; Sarada Subramanian; Suvarna Alladi (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring, 2025)
Abstract INTRODUCTION The rising dementia burden and limited knowledge of fluid biomarkers in South Asians highlights this study's aim on evaluating their utility for the diagnosis of Alzheimer's disease and related dementias (ADRD). METHODS Participants with ADRD were recruited from a cognitive disorders clinic in India. We performed cognitive assessments and severity evaluations using standard tests. Serum and cerebrospinal fluid (CSF) levels of glial fibrillary acidic protein (GFAP), neurofilament light chain (NfL), total tau, and ubiquitin C‐terminal hydrolase L1 (UCHL1) were quantified using a Simoa HD analyzer. RESULTS Among the 101 participants, serum GFAP and NfL levels were significantly greater in dementia participants (n = 70) than controls. Serum biomarkers significantly correlated with their corresponding CSF levels. Significant correlations were noted for serum and CSF GFAP and NfL in Alzheimer's disease (ρ = 0.492, 0.664) and between serum and CSF NfL in frontotemporal dementia (ρ = 0.727). Serum GFAP, NfL, and UCHL1 demonstrated high diagnostic accuracy (area under the curve = 0.765–0.806). DISCUSSION Our results emphasize the role of fluid biomarkers in diagnosing dementia in low‐resource settings in South Asians. Highlights Serum glial fibrillary acidic protein (GFAP) and neurofilament light chain (NfL) levels were significantly greater in patients with dementia than in healthy controls. Significant correlation was observed between the serum and cerebrospinal fluid levels of GFAP, NfL, and total tau independent of the baseline demographics or co‐morbidities, indicating their potential role in clinical practice. Serum biomarker levels were related to the severity of dementia. This is one of few studies on fluid‐based biomarkers in diverse cohorts with Alzheimer's disease and related dementias in the South Asian cohort with limited resources.